On‐Surface Synthesis and Characterization of Acene‐Based Nanoribbons Incorporating Four‐Membered Rings. Issue 52 (8th July 2019) - Sánchez‐Sánchez, Carlos; Dienel, Thomas; Nicolaï, Adrien; Kharche, Neerav; Liang, Liangbo; Daniels, Colin; Meunier, Vincent; Liu, Junzhi; Feng, Xinliang; Müllen, Klaus; Sánchez‐Valencia, Juan Ramón; Gröning, Oliver; et al.
Abstract: A bottom up method for the synthesis of unique tetracene‐based nanoribbons, which incorporate cyclobutadiene moieties as linkers between the acene segments, is reported. These structures were achieved through the formal [2+2] cycloaddition reaction of ortho ‐functionalized tetracene precursor monomers. The formation mechanism and the electronic and magnetic properties of these nanoribbons were comprehensively studied by means of a multitechnique approach. Ultra‐high vacuum scanning tunneling microscopy showed the occurrence of metal‐coordinated nanostructures at room temperature and their evolution into nanoribbons through formal [2+2] cycloaddition at 475 K. Frequency‐shift non‐contact atomic force microscopy images clearly proved the presence of bridging cyclobutadiene moieties upon covalent coupling of activated tetracene molecules. Insight into the electronic and vibrational properties of the so‐formed ribbons was obtained by scanning tunneling microscopy, Raman spectroscopy, and theoretical calculations. Magnetic properties were addressed from a computational point of view, allowing us to propose promising candidates to magnetic acene‐based ribbons incorporating four‐membered rings. The reported findings will increase the understanding and availability of new graphene‐based nanoribbons with high potential in future spintronics. Abstract : Acene‐based nanoribbons : The on‐surface synthesis and characterization of the electronic and magnetic properties of unprecedented tetracene‐based nanoribbons was addressed by a combination of scanning probe microscopy (SPM) experimental techniques and theoretical calculations.